International data transfer. An analysis of schrems cases I and II - Sakamoto, Maria Laura Grisi (Seven Editora, 2023)
Addressing the current technology landscape, the internet, and the devices that are connected play a key role. Today’s media open up a range of opportunities for man to present ideas, business, and forms of interaction[1]To make these interactions, we can understand that the transfer of countless amounts of data between one person and another is quite significant, so let us think about international data transfers and what their impacts on the world economy are. Here, the aim is to address the issue of international data transfer and discuss important decisions that directly interfere with the business made between the United States and the European Union, which also reflects on the global economy. FINKELSTEIN, Claudius. MALUF, Fernando. New Technologies and Constitutional Barriers to Economic Intervention by Public Administration. DOI: https://doi.org/10.56238/devopinterscie-092